Analysis of the Effect of Economic Growth and Labor Force Growth on Unemployment Rates in Indonesia - Saharuddin, Saharuddin; Ali, Muhammad (Program Magister Administrasi Publik, 2024)
Time Series from 2000 to 2021 on the variables Economic Growth and Labor Force Growth on the Unemployment Rate in Indonesia. The analytical method used is Multiple Linear Regression. The results of the research show that economic growth (X1), Labor Force Growth (X2), are constant, so the unemployment rate (Y) is -88.33%. The economic growth variable (X1) has a value of 0.01, which means that if economic growth (X1) increases by 1%, the unemployment rate (Y) will decrease by 0.01% assuming that labor force growth is constant. the labor force growth variable (X2) has a value of 1.41. This means that if labor force growth (X2) increases by 1%, the unemployment rate (Y) will decrease by 1.41% assuming constant economic growth.